1993
DOI: 10.1002/j.2050-0416.1993.tb01173.x
|View full text |Cite
|
Sign up to set email alerts
|

Pitching Rate in High Gravity Brewing

Abstract: The optimal pitching rate in high gravity worts (12-16°P) was about 0.3 g/l wet weight (2.3 x 106 counted cells/ml) and per one percent of original wort gravity. In very high gravity worts (20-23°P) the corresponding figure was 0.4 g/l (2.9 x 10* cells/ml). Higher amounts of yeast did not improve the fermentation rate.With increased original wort gravity, flocculation of the yeast weakened and the amount of cropped yeast decreased. The viability of the crop yeast was good.In the conditions used, excessive prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 5 publications
3
26
0
Order By: Relevance
“…The fermentations were performed at 12°C for each yeast strain and the gravity monitored daily. The pitching rates were 4, 6 and 8 g (wet weight)·L -1 for the 10.9, 16.5 and 23.7°P wort, respectively 27 .…”
Section: Wort Preparation and Fermentationmentioning
confidence: 97%
“…The fermentations were performed at 12°C for each yeast strain and the gravity monitored daily. The pitching rates were 4, 6 and 8 g (wet weight)·L -1 for the 10.9, 16.5 and 23.7°P wort, respectively 27 .…”
Section: Wort Preparation and Fermentationmentioning
confidence: 97%
“…The slowest fermentation rate was with spontaneous fermentation without inoculation. Several workers 12,17,20,32 have stated that increasing the inoculum level resulted in a faster fermentation rate with brewer's and wine yeast strains.…”
Section: Effect Of Inoculum Level On the Course Of Fermentationmentioning
confidence: 99%
“…Although there are various studies on the effects of pitching levels of brewer's yeasts on beer fermentation 12,30,32 , information concerning the effects of the pitching level of the wine yeast S. cerevisiae on wine fermentation is scarce. Mateo et al 20 found that inoculum levels affected wine fermentation and volatiles.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal brewing yeast should exhibit constant flocculation characteristics during consecutive rounds of fermenting, cropping, storing and repitching. Improved and reproducible flocculation is currently important because many breweries are using increasingly high-gravity worts, which are believed to be associated with sub-optimal yeast sedimentation 92 . The present review targets practical aspects of yeast flocculation that are relevant to brewer's yeast strains under industrial brewery conditions.…”
Section: Introductionmentioning
confidence: 99%